Molecular Findings Before Vision Loss in the Streptozotocin-Induced Rat Model of Diabetic Retinopathy - Mădălina Moldovan; Roxana-Denisa Capraș; Raluca Paşcalău; Gabriela Adriana Filip (Current Issues in Molecular Biology)
The streptozotocin-induced rat model of diabetic retinopathy presents similarities to the disease observed in humans. After four weeks following the induction of diabetes, the rats experience vision impairment. During this crucial four-week period, significant changes occur, with vascular damage standing out as a clinically significant factor, alongside neovascularization. While redox imbalance, activation of microglia, secretion of pro-inflammatory cytokines, and neuronal cell death are also observed, the latter remains an emerging hypothesis requiring further exploration. This review is a comprehensive and up-to-date chronological depiction of the progression of diabetic retinopathy within the initial four weeks of hyperglycemia, which precede the onset of vision loss. The data are structured in weekly changes. In the first week, oxidative stress triggers the activation of retinal microglia, which produces inflammation, leading to altered neurotransmission. The second week is characterized by leukostasis, which promotes ischemia, while neural degeneration begins and is accompanied by a simultaneous increase in vessel permeability. The progression of redox and inflammatory imbalances characterized the third week. Finally, in the fourth week, significant developments occur as vessels dilate and become tortuous, neovascularization develops, and retinal thickness diminishes, ultimately leading to vision loss. Through this clearly structured outline, this review aims to delineate a framework for the progression of streptozotocin-induced diabetic retinopathy.